COMPARATIVE ANALIYSIS OF MOTOR ABILITIES OF STUDENTS FROM URBAN AND RURAL AREAS - Goran Tadić; Gorica Bilak; Radenko Dobraš (Sport Scientific And Practical Aspects, 2025)
Urbanization and modernization of villages has led to digitization, internet and social networks in rural areas generally do not lag behind in comparison to urban areas, and so the effect we have is fewer young people who participate in the work on the farm and other rural activities. Objective of this research is to determine whether there are statistically significant differences in motor variables between male and female pupils, early school age, who live and go to school in urban and rural areas in the municipality of Modriča. The research was conducted throughout two identical tests ranging one year, precisely in May 2011 and in May 2012. The number of questioned children was 351 male and female pupils at the fourth and fifth grades Primary school „Sveti Sava“ from Modriča and its regional rural departments. All the questioned were tested by battery tests „EUROFIT“, and analyzed in seven variables in the field of motor abilities. Based on the results it was concluded that in the majority of the tested variables no statistically significant differences i motor abilities between male and female pupils early school age who live and go to school in urban and rural areas. Minor differences that emerged in the first and second test in certain variables are in favor of the male and female pupils from urban areas, and it is presumed that is a consequence of larger choice of activities which they can find in urban environment.